Conducta obstétrica ante embarazo de 31 semanas más desprendimiento prematuro de placenta más óbito fetal. - Bricio Quintana, Andrea Julyssa (2021)
Placental abruption is the partial or complete separation of a placenta, it is normally inserted before the onset labor. This occurs in a rage of 0.4- 1% of pregnancy. This pathology is associated with a high maternal fetal morbidity and mortality. As a consequence, a study and a follow up related to this pathology in the case of a 33-year-old grand multipara patient with Premature Detachment of Placenta and Pregnancy of 31 weeks with single fetus and absent fetal heart rate, the same that was presented at the Basic Hospital Dr. Rafael Serrano Lopez. Diagnosis is based primarily on clinical manifestations. The use of ultrasound has a limited utility for diagnosis due to its low sensitivity. The attitude will be conditioned by the maternal and fetal state as well as the degree of placental abruption and the gestational age at the time of diagnosis. This document reflects the situation healthcare professional and women face, due to the placental abruption at 31 weeks gestation, therefore, the immediate termination of pregnancy due to fetal-death.